The Minimum Effective Training Dose Required for 1RM Strength in Powerlifters - Androulakis-Korakakis, Patroklos; Michalopoulos, Nick; Fisher, James P.; Keogh, Justin; Loenneke, Jeremy P.; Helms, Eric; Wolf, Milo; Nuckols, Greg; Steele, James (Frontiers in Sports and Active Living, 2021)
The aim of this multi-experiment paper was to explore the concept of the minimum effective training dose (METD) required to increase 1-repetition-maximum (1RM) strength in powerlifting (PL) athletes. The METD refers to the least amount of training required to elicit meaningful increases in 1RM strength. A series of five studies utilising mixed methods, were conducted using PL athletes & coaches of all levels in an attempt to better understand the METD for 1RM strength. The studies of this multi-experiment paper are: an interview study with elite PL athletes and highly experienced PL coaches (n = 28), an interview and survey study with PL coaches and PL athletes of all levels (n = 137), two training intervention studies with intermediate-advanced PL athletes (n = 25) and a survey study with competitive PL athletes of different levels (n = 57). PL athletes looking to train with a METD approach can do so by performing 3–6 working sets of 1–5 repetitions each week, with these sets spread across 1–3 sessions per week per powerlift, using loads above 80% 1RM at a Rate of Perceived Exertion (RPE) of 7.5–9.5 for 6–12 weeks and expect to gain strength. PL athletes who wish to further minimize their time spent training can perform autoregulated single repetition sets at an RPE of 9–9.5 though they should expect that strength gains will be less likely to be meaningful. However, the addition of 2–3 back-off sets at 80% of the single repetitions load, may produce greater gains over 6 weeks while following a 2-3-1 squat-bench press-deadlift weekly training frequency. When utilizing accessory exercises in the context of METD, PL athletes typically utilize 1–3 accessory exercises per powerlift, at an RPE in the range of 7–9 and utilize a repetition range of 6–10 repetitions.